Correction: Benchmark thermochemistry of chloramines, bromamines, and bromochloramines: halogen oxidants stabilized by electron correlation. Issue 45 (3rd November 2016) - Trogolo, Daniela; Arey, J. Samuel
Abstract : Correction for 'Benchmark thermochemistry of chloramines, bromamines, and bromochloramines: halogen oxidants stabilized by electron correlation' by Daniela Trogolo et al., Phys. Chem. Chem. Phys., 2015, 17, 3584–3598.